'I know they are not trained in dementia': Addressing the need for specialist dementia training for home care workers. (23rd October 2019) - Polacsek, Meg; Goh, Anita; Malta, Sue; Hallam, Brendan; Gahan, Luke; Cooper, Claudia; Low, Lee‐Fay; Livingston, Gill; Panayiotou, Anita; Loi, Samantha; Omori, Maho; Savvas, Steven; et al.
Abstract: Global population ageing has meant a rapid increase in the numbers of older people with dementia, most of whom live in their own homes. Staying at home is an important determinant of health and well‐being. As care needs increase, the quality of community support which older people receive directly influences their capacity to remain in their own homes. While many are supported informally by family carers, formal support provided by home care workers often enables them to remain at home for longer period. However, providing community‐based care for people with dementia can be challenging. Workers often lack training in dementia‐specific care for clients with increasingly complex needs, and typically work without direct supervision. As the demand for person‐centred home care for people with dementia increases, specialist dementia training for home care workers is urgently needed. In this qualitative study, we used in‐depth interviews of a purposive sample, comprising 15 family carers and four older people with dementia, to understand the experience of receiving community care. Data analysis was guided by Braun and Clarke's approach to thematic analysis and revealed the following five overlapping themes, relating to home care workers' understanding of dementia, person‐centred care, communication and rapport, mutual collaboration, and the influence of organisational constraints on continuity of care. Although participants acknowledged that service providers operated under challenging circumstances, they were frustrated with home care workers' lack of dementia knowledge and inconsistent staff rostering. Conversely, an understanding of the lived experience of dementia, effective communication and rapport, and continuity of care contributed significantly to a positive experience of receiving care. The findings of this study will be used to inform the essential elements of a training program aimed at enabling and empowering a skilled, specialist home care workforce to support older people with dementia to live well at home for as long as possible.